TEAM COOPERATION AND ITS IMPLICATIONS ON IMPROVING QUALITY OF EDUCATION IN SCHOOL - Siti Rochanah Siti Rochanah (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
This research aims to know and to obtain an overview of quality of education improvement through teamwork in SMKN 48 Jakarta. This research was conducted in June until September 2016. The approach used is a qualitative approach with descriptive method. Data collection was done through an interview, observation, and study documentation. Data are from principal’s and supported teachers as informants. Based on the results of research and data analysis, it can be concluded that teamwork have a very dominant role in improving the quality of the school. Teamwork formed by the principal's consist of teachers, committee and parents. The team's success can be seen from the many achievements that have been attained by the students and the school. Coordination happens in teams always do good communication and mutual help to each other. As the main actors in the school in improving the quality of education, the principal's needs to improve its ability to instruct the task, the participation and control of the situation. The principal's orientation in involving the various parties in the activities that advance the quality of schools in developing a culture of discussion is the action that had been very precise. Through the teamwork the quality of education in these schools be increased.